Anticancer innovative therapy: Highlights from the ninth annual meeting. (February 2020) - Volpari, T.; De Santis, F.; Bracken, A.P.; Pupa, S.M.; Buschbeck, M.; Wegner, A.; Di Cosimo, S.; Lisanti, MP.; Dotti, G.; Massaia, M.; Pruneri, G.; Anichini, A.; et al.
Abstract: The Ninth Annual Conference of "Anticancer Innovative Therapy", organized by Fondazione IRCCS Istituto Nazionale dei Tumori di Milano (Fondazione IRCCS INT) and hosted by Hotel Michelangelo, was held in Milan on 25 January 2019. Cutting-edge science was presented in two main scientific sessions: i ) pre-clinical evidences and new targets, and ii ) clinical translation. The Keynote lecture entitled "Cancer stem cells (CSCs): metabolic strategies for their identification and eradication" presented by M. Lisanti, was one of the highlights of the conference. One key concept of the meeting was how the continuous advances in our knowledge about molecular mechanisms in various fields of research (cancer metabolism reprogramming, epigenetic regulation, transformation/invasiveness, and immunology, among others) are driving cancer research towards more effective personalized antineoplastic strategies. Specifically, recent preclinical data on the following topics were discussed: 1. Polycomb group proteins in cancer; 2. A d16HER2 splice variant is a flag of HER2 addiction across HER2-positive cancers; 3. Studying chromatin as a nexus between translational and basic research; 4. Metabolomic analysis in cancer patients; 5. CDK4-6 cyclin inhibitors: clinical activity and future perspectives as immunotherapy adjuvant; and 6. Cancer stem cells (CSCs): metabolic strategies for their identification and eradication. In terms of clinical translation, several novel approaches were presented: 1. Developing CAR-T cell therapies: an update of preclinical and clinical development at University of North Carolina; 2. Vγ9Vδ2 T-cell activation and immune suppression in multiple myeloma; 3. Predictive biomarkers for real-world immunotherapy: the cancer immunogram model in the clinical arena; and 4. Mechanisms of resistance to immune checkpoint blockade in solid tumors. Overall, the pre-clinical and clinical findings presented could pave the way to identify novel actionable therapeutic targets to significantly enhance the care of persons with cancer.